2002
DOI: 10.1111/1469-7610.00076
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime sleep‐wake patterns and self‐soothing from birth to one year of age: a longitudinal intervention study

Abstract: Background-The objectives of this study were to: (1) describe the longitudinal development of sleep-wake patterns of solitary-sleeping infants from 1 to 12 months of age, (2) identify effects on sleep patterns and on self-soothing behaviors of introducing a novel sleep aid, and (3) identify predictive factors of self-soothing at 12 months using a transactional model as a guide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
168
6
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(200 citation statements)
references
References 39 publications
23
168
6
3
Order By: Relevance
“…Furthermore, our results are contrary to the results of a longitudinal study in which caregiver self-efficacy was negatively associated with the child´s self-soothing competence [32]. The authors argued that lower self-efficacy leads to less responsiveness and thus promotes selfsoothing of the child.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results are contrary to the results of a longitudinal study in which caregiver self-efficacy was negatively associated with the child´s self-soothing competence [32]. The authors argued that lower self-efficacy leads to less responsiveness and thus promotes selfsoothing of the child.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies Besides coping, parental self-efficacy seems to be a relevant factor that modulates parental behavior related to the child´s sleep situation. Prospective data showed that higher caregiver self-efficacy was linked to more self-soothing competence of the child one year later [32]. Furthermore, studies indicate that parental training of an infant´s sleep behavior is associated with an increase in their self-efficacy [33].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the children (169, 56%) slept in the same room with their parents, but in separate beds, 28.0% (84) slept in their own room with a sibling, and 7.7% (23) The majority of families (247, 82%) did routine preparations before sleeping. The most common practice was to feed the child (145, 48.3%), followed by changing the diaper (100, 33.3%), taking the child to bed (88, 29.3%), singing a lullaby (72, 24%), rocking the cradle (72, 24%), and holding the child on their lap (71, 23.7%).…”
Section: Resultsmentioning
confidence: 99%
“…22 Previous studies showed that night waking problems in children were related to the child's nature, family, cultural differences, and stressful life conditions. 5,23 The frequency of night waking is also related to breastfeeding, sleeping in the same room with the parents, bottle-feeding, taking the child to the parental bed, and regular fulfilment of bedtime routines. 14,24,25 In the present study, practices such as breastfeeding, giving milk or food, and soothing the child on lap if waking crying at night were very common.…”
Section: Discussionmentioning
confidence: 99%
“…These practices included parental presence at bedtime (Adair, Bauchner, Phillip, Levenson, & Zuckerman, 1991;Mindell, Meltzer, Carskadon, & Chervin. 2009), inconsistency in where the infant slept at night (Atkinson, Vetere, & Grayson, 1995), putting the infant down in her/his bed after, rather than before, s/he fell asleep (Burnham, Goodlin-Jones, Gaylor, & Anders, 2002;DeLeon & Karraker, 2007), short latency of response to nighttime crying (Burnham et al, 2002), infant sleeping with the parent (Burnham et al, 2002;DeLeon & Karraker, 2007;Johnson, 1991;Mao, Burnham, Goodlin-Jones, Gaylor, & Anders, 2004;Mindell, Sadeh, Kohyama, & How, 2010), breastfeeding (DeLeon & Karraker, 2007;Johnson, 1991;Mindell, Sadeh, Kohyama, & How, 2010;Tikotzky, Sadeh, & Glickman-Gavrieli, 2010), and active physical comforting and close contact (Morrell, & Cortina-Borja, 2002;Morrell & Steele, 2003).…”
Section: Maternal Depression and Infant Night Wakingmentioning
confidence: 99%